Efficacy and safety of etrolizumab in the treatment of inflammatory bowel disease: a meta-analysis - Dai, Yong gang; Sun, Dajuan; Liu, Jiahui; Wei, Xiunan; Chi, Lili; Wang, Hongya (PeerJ, 2024)
Background To explore the efficacy and safety of etrolizumab in treating inflammatory bowel disease (IBD) through meta-analysis. Method A comprehensive exploration encompassed randomized controlled trials examining the efficacy of etrolizumab in treating IBD across PubMed, Embase, Cochrane library, and Web of Science, with a search deadline of 1 December 2023. Quality assessment leaned on the Cochrane manual’s risk-of-bias evaluation, while Stata 15 undertook the data analysis. Result Five randomized controlled studies involving 1682 individuals were finally included, Meta-analysis results suggested that compared with placebo, etrolizumab could improve clinical response (RR = 1.26, 95% CI [1.04–1.51]), clinical remission (RR = 1.26, 95% CI [1.04–1.51]) in IBD patients. Endoscopic alleviate (RR = 2.10, 95% CI [1.56–2.82]), endoscopic improvement (RR = 2.10, 95% CI [1.56–2.82]), endoscopic remission (RR = 2.10, 95% CI [1.56–2.82]), Endoscopic improvement (RR = 1.56, 95% CI [1.30–1.89]), histological remission (RR = 1.62, 95% CI [1.26–2.08]), and did not increase any adverse events (RR = 0.95, 95% CI [0.90–1.01]) and serious adverse events (RR = 0.94, 95% CI [0.68–1.31]). Conclusion According to our current study, etrolizumab is a promising drug in IBD.
Keywords: Etrolizumab; Inflammatory bowel disease; Ulcerative colitis; Crohn’s disease; Meta-analysis